The Effect of Tourist Visits and Investment on Economic Growth (Efficient: Indonesian Journal of Development Economics, 2022)
This study aims to analyze economic growth in Central Java Province; with the independent variables, namely the number of tourist visits in districts and cities in Central Java; investment in districts and cities in Central Java; and unemployment in urban districts in Central Java as intervening variables. This research uses quantitative research. The data used in this research is secondary data. The data analysis method uses path analysis (Path Analysis). The results showed that (1) tourist visits had no significant effect on unemployment; (2) Investment has a positive and significant effect on unemployment; (3) tourist visits have a positive and significant impact on economic growth directly; (4) investment has a positive and significant impact on economic growth directly; (5) unemployment has a positive and significant effect on economic growth; (6) tourist visits do not affect economic growth through unemployment; (7) investment has an effect on economic growth through unemployment. Penelitian ini bertujuan untuk menganalisis pertumbuhan ekonomi di Provinsi Jawa Tengah; dengan variabel bebasnya yaitu jumlah kunjungan wisatawan di kabupaten dan kota di Jawa Tengah; investasi di kabupaten dan kota di Jawa Tengah; dan pengangguran pada kabupaten kota di Jawa Tengah sebagai variabel intervening. Penelitian ini menggunakan jenis penelitian kuantitatif. Data yang di gunakan dalam penelitian ini adalah data sekunder. Metode analisis data mengunakan analaisis jalur (Path Analisis). Hasil penelitian menunjukkan bahwa (1) kunjungan wisatawan tidak berpengaruh signifikan terhadap pengangguran; (2) Investasi berpengaruh positif dan siginifikan terhadap pengangguran; (3) kunjungan wisatawan berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi secara langsung; (4) investasi berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi secara langsung; (5) pengangguran berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi; (6) kunjungan wisatawan tidak bengaruh terhadap pertumbuhan ekonomi melalui pengangguran; (7) investasi berpengaruh terhadap pertumbuhan ekonomi melalui pengangguran.